Cities and Citadels An Archaeology of Inequality and Economic Growth - Green, Adam; Wilkinson, Toby; Wilkinson, Darryl; Highcock, Nancy; Leppard, Thomas (Taylor & Francis, 2024)
Cities and Citadels provides an urgent update of archaeology's engagement with economic theory. Recent events have forced a major reassessment of economic thinking. In the wake of the 2008 Great Recession and the economic impact of the COVID-19 Pandemic, the world finds itself in unprecedented times. Even though archaeology typically concerns itself with the remote past, it must also help us understand how we got to where we are today. This book takes up the challenging new theories of scholars like Thomas Piketty, Mariana Mazzucato and David Graeber and explores their importance for the study of human economies in ancient and prehistoric contexts. Drawing on case studies from the Neolithic to the Classical Era and spanning the globe, the authors put forward a new narrative of economic change that is relevant to the 21st century. This book speaks to the study of economics in all ancient societies and is suitable for researchers of archaeology, economics, economic history and all related disciplines.